Kegiatan Pengabdian Masyarakat dalam Rangka Peningkatan Kewaspadaan Masyarakat terhadap Penyakit Pre-Diabetes dan Diabetes Mellitus Tipe II dengan Edukasi dan Deteksi Dini Penyakit - Siufui Hendrawan; Anggita Tamaro; Chesia Angelina; Yohanes Firmansyah (Jurnal Pengabdian Ilmu Kesehatan, 2023)
Pre-diabetes and type 2 diabetes mellitus are two conditions associated with impaired glucose metabolism in the body, in which blood sugar levels become higher than normal. Pre-diabetes is a condition that often doesn't cause symptoms, so it's often not diagnosed early. However, pre-diabetes can be a risk factor for type 2 diabetes mellitus, heart disease, and stroke. Community outreach, education, and early detection of prediabetes and type 2 diabetes mellitus have an important role in efforts to prevent and control these diseases. Community outreach and education can increase awareness about prediabetes and type 2 diabetes mellitus and the risk factors that influence the occurrence of these conditions. This community service activity was carried out in May 2023 by involving 52 productive age respondents. All respondents attended a series of counseling, physical examinations, and supporting examinations related to diabetes mellitus and its complications. The results of this community service revealed that 8 (15.4%) respondents had a GDP ≥ 126 mg/dL and 22 (42.3%) respondents had a GDP 100 - 125 mg/dL. Checking blood sugar levels regularly can also help in early detection of disease. By raising awareness and promoting early detection, it can help reduce the burden of disease and the costs incurred by individuals and society as a whole. In addition, preventing prediabetes and type 2 diabetes mellitus can also help prevent more serious complications such as heart disease, stroke and kidney failure. By preventing or controlling prediabetes and type 2 diabetes mellitus, people can maintain a better quality of life and avoid complications that can affect quality of life. This can help increase the productivity and welfare of society as a whole.